Low-grade endometrial stromal sarcoma - Reyna-Villasmil, Eduardo (2022)
Endometrial stromal sarcoma is a rare malignant neoplasm that originates in theendometrial stroma. It can have several forms of differentiation, including smoothmuscle and sex cord. Low-grade endometrial stromal sarcoma is a rare type of endometrial tumor, constituting only 0.2% of all uterine neoplasms. Its etiology isunknown, but some cases are associated with obesity, polycystic ovary syndrome,diabetes mellitus, early menarche, and estrogen replacement therapy or tamoxifen.Symptomatology is nonspecific, ranging from pelvic pain to progressive abnormalgenital bleeding, and is difficult to recognize by radiological imaging. In most cases, the diagnosis is made by pathological evaluation. Immunohistochemical staining canalso help differentiate it from other neoplasms. Therefore, it is important to have a high index of suspicion for this type of rare neoplasm. Its treatment is surgicaland its follow-up should be long term, due to the high risk of late recurrences andmetastasis. A case of low-grade endometrial stromal sarcoma is presented.